Treatment of Class II Malocclusion With Orthodontic Microimplant Anchorage - Huanhuan Zhao; Ru Sun; Sumin Cao; Jingmei Han (Elsevier, 2024)
Introduction: The objective of the study was to compare the effects of orthodontic microimplant anchorage (MIA) and conventional extraoral arch anchorage (EAA) on tooth structure and oral inflammatory response in patients with Class II Division I malocclusion. Methods: A total of 104 patients with Class II malocclusion were enrolled and were randomly assigned to receive MIA or EAA treatments. Clinical efficacy was assessed at 6 months after treatment by measuring molar shift, convex distance, and hinge angle difference between maxillary and mandibular incisors. X-ray was performed for tissue evaluations. The levels of cell adhesion molecule-1 (CAM-1), matrix metalloproteinase-2 (MMP-2), and proinflammatory cytokines in gingival sulcus fluid were measured using enzyme-linked immunosorbent assay to assess inflammatory responses to the implants. Results: Our study demonstrated superior efficacy of MIA compared to EAA in terms of overall efficacy, molar shift, convex distance between upper and middle incisors, as well as hinge angle difference between upper and middle incisors. MIA also showed greater efficacy in reducing tissue fix-point measurements, including saddle point-nasal root point-superior alveolar seat point (SNA), alveolar seat point-nasal root point-inferior alveolar seat point (ANB), overlying (OJ), and overbite (OB). Conclusions: MIA is a novel orthodontic treatment that showed stronger efficacy in inducing molar shift and correcting soft/hard tissue positions, whilst generating suppressed inflammatory responses. Our study could have significant implications for practice in the orthodontic treatment of Class II malocclusion.